Tuning of PIDD2 controllers for oscillatory systems with time delays - Xingqi, Hu; Guolian, Hou; Wen, Tan (Frontiers in Control Engineering, 2023)
PID control is a durable control technology that has been widely applied in the process control industry. However, PID controllers cannot achieve satisfactory performance for oscillatory systems with long time delays, thus high-order controllers (PIDD2) can be adopted to enhance the control performance. In this paper we propose a tuning formula for PIDD2 controller for oscillatory systems with time delays and its practical implementation via an observer-bandwidth-based state-space PIDD2. Simulation results show that the state-space PIDD2 controller tuned from the proposed formula trades-off among robustness, time domain performance, and measurement noise attenuation, and can arrive at a better control effect compared with PID for oscillatory systems.